Juridical Analysis of Banking Authority In Blocking Accounts Indicated For Online Gambling: The Conflict Between The Prudential Principle and Customer Protection - Simanjuntak, Jimmy (Indonesian Journal Publisher, 2026)
This research examines the juridical clash between the mandatory authority of banks to block suspicious accounts and the constitutional rights of customers to legal certainty and property protection. Utilizing a normative legal research method with statutory and conceptual approaches, this study analyzes the implementation of Law Number 8 of 2010 and POJK Number 8 of 2023. The findings reveal that heavy reliance on automated Artificial Intelligence (AI) monitoring systems creates a significant risk of